Thresholds of ultrasound synovial abnormalities for knee osteoarthritis – a cross sectional study in the general population. Issue 3 (March 2019) - Sarmanova, A.; Hall, M.; Fernandes, G.S.; Valdes, A.M.; Walsh, D.A.; Doherty, M.; Zhang, W.
Summary: Objective: To establish "normal" ranges for synovial thickness and effusion detected by ultrasound (US) and to determine cut-offs associated with knee pain (KP) and radiographic knee osteoarthritis (RKOA) in the community. Methods: 147 women and 152 men ≥40 years old were randomly selected from the Nottingham KP and Related Health in the Community (KPIC) cohort ( n  = 9506). The "normal" range was established using the percentile method in 163 participants who had no KP and no RKOA. Optimal (maximum sensitivity and specificity) and high specificity (90%) cut-offs were established using receiver operating characteristic (ROC) curve analysis in a comparison between people with both KP and RKOA and normal controls. Results: Effusion and synovial hypertrophy differed by gender but not by age or laterality, therefore gender-specific reference limits were estimated. However, the "normal" ranges between men and women were similar for effusion (0–10.3 mm vs 0–9.8 mm), but different for synovial hypertrophy (0–6.8 mm vs 0–5.4 mm). Power Doppler Signal (PDS) in the healthy controls was uncommon (1.2% in men and 0.0% in women). The optimal cut-off was 7.4 mm for men and 5.3 mm for women for effusion, and 3.7 and 1.6 for hypertrophy respectively. The high specificity cut-off was 8.9 for men and 7.8 for women for effusion, and 5.8 and 4.2 for hypertrophy respectively. Conclusions: US effusion and synovial hypertrophy but not PDS are common, but differ by gender, in community-derived people without painful knee OA. Currently used cut-offs for abnormality need reappraisal.